Pengaruh Job Rotation, Komitmen Organisasi, dan Kepuasan Kerja Terhadap Kinerja Karyawan Bagian Administrasi Pada CV. Agro Mulia Surabaya - Dita Anggraini Puspita Sari; Tri Andjarwati (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to prove and analyze the influence of Job Rotation, Organizational Commitment and Job Satisfaction which have a significant effect on the performance of administrative employees at CV. Agro Mulia Surabaya. The type of research used is quantitative research. The data collection method uses a questionnaire and uses a Likert scale as an answer. Sampling used saturated samples and SPSS 29 as an analysis tool. The data source used is primary data. The sample population is employees in the administration section of CV. Agro Mulia Surabaya totaling 41 employees. Based on the results of data analysis, it shows that job rotation has a significant effect on the performance of administrative employees at CV. Agro Mulia Surabaya; Organizational Commitment has a significant effect on the performance of administrative employees at CV. Agro Mulia Surabaya; and Job Satisfaction has a significant effect on the performance of administrative employees at CV. Agro Mulia Surabaya.